Redes sociales y la publicidad de los servicios del Instituto Ecuatoriano de Seguridad Social (IESS), Babahoyo - Ortega Almeida, Hillary Nayely (2023)
In this research project, we address the issue of the lack of official presence of the Instituto Ecuatoriano de Seguridad Social (IESS) Babahoyo on social media, which affects the dissemination of information about the healthcare and social security services offered by this institution. It is recognized that social media plays a crucial role in contemporary communication and advertising, especially in reaching a more tech-savvy audience with less time for television. The overall objective is to determine how social media influences the advertising of IESS Babahoyo's services, with specific goals including analyzing the importance of social media in service delivery, identifying benefits for affiliates, and demonstrating its feasibility in advertising. This study aligns with the research field of Communication and Information Technology, focusing on communication processes and phenomena in society. The beneficiaries of this research are citizens, businesses, and IESS itself, as it is expected to enhance communication and promote greater affiliation with social security services through more effective social media strategies.